(untitled) (Herald of Journalism, 2016)
В статье анализируется казахскоязычное интернет-пространство. До сих пор не разработаны обучающие программы на государственном языке по созданию сайтов, блогов, а также социальных страниц, что ограничивает активизацию пользова -телей Казнета на государственном языке. Если эти проекты будут правильно реализованы, то казахскоязычное интернет про -странство станет шире. The article analyzes the Kazakh-web-space. For example, there is still no approved terms in the state language. It is still not developed training programs in the official language for creating websites, blogs and social pages, which limits the activation of Kaznet users in the state language. Several years ago, the state embarked on a project to computerize villages. And now comes the In ternet already up to distant villages. If these projects are properly implemented, then, of course, Kazakh -web space will be slightly wider. However, this is not so fast. And we, in turn, should use the Internet not only to obtain information, but must also pay its share of useful and necessary information on the Kazakh-internet. None of this does not prevent us, in our hands.